Multichannel Retail Environment: Opportunities And Challenges / Norzieiriani Ahmad and Muhammad Rizwan - Ahmad, Norzieiriani; Rizwan, Muhammad (Universiti Teknologi MARA, Kedah, 2019)
A seamless customer shopping experience has been provided in a multichannel environment. Currently, firms are using various shopping channels to enhance the customer satisfaction. Customers can use various channels like traditional physical stores, internet-based stores and social media as well to complete their shopping tasks. A large number of people embracing the innovative multichannel environment for information sharing in different online and offline channels. Now a days, these customers require a tailored experience and major portion of these customers demand from the firms to provide a customized solution for their purchasing needs. Consequently, the firms acknowledged the current demands of the customers and opening multiple channels to cater these customers preferences, recording their purchasing history and customer data from multiple channels to provide them an innovative shopping experience. The instant success of these multichannel firms forced the other firms to open multiple channels to boost their image and enjoy higher customer satisfaction and loyalty. However, increasing the number of channels in a firm require a close coordination strategy and synergy among these channels. Channel integration is a possible solution for managing these multiple channels to create a complementary effect.